The Effect of Downstream Policies, Exchange Rates, Production and International Prices on Indonesia's Nickel Export Volume with Global Demand as a Mediator Variable for the 2015-2024 Period - Dewi Ayu Safitri; Denny Saputera (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The increase in world nickel demand has prompted the Indonesian government to implement downstream policies to increase the added value of mineral commodities before they are exported to the international market. This study aims to analyze the influence of downstream policies, exchange rates, production levels, and international prices on Indonesia's nickel export volume with global demand as a mediating variable. The research uses a quantitative approach with secondary data for the period 2015–2024 obtained from various official institutions such as the Central Statistics Agency, Bank Indonesia, TradeMap, and the World Trade Organization. The analysis was carried out based on international trade theory, comparative advantage theory, Heckscher-Ohlin theory, value-added theory, and derived demand theory. The results of the study show that the downstream policy contributes to increasing the competitiveness of Indonesia's nickel exports through increasing the added value of products. Production levels have an important influence in maintaining the sustainability of export supply, while exchange rates and international prices affect the competitiveness of Indonesian products in the global market. Global demand has proven to be a mechanism that strengthens the relationship between these variables and export volumes. The findings of the study show that the success of Indonesia's nickel exports is not only determined by production and price factors, but also influenced by government policies and international market dynamics.